Analysis on The Effectiveness of Key Account Management Implementation in The Poultry Industry in Indonesia: The Key Accountâ€™s Point of View - Wahyuni, Wully; Titus, Amol (The Indonesian Journal of Business Administration, 2013)
Trust in supplier is very important to feed producers in Indonesian poultry industry. This study is trying to understand if the key account management is an effective approach made by the supplier and to find out the underlying principle that drives the success of the implementation. There is a positive correlation between relational behavior construct with the satisfaction level of relationship quality. This study confirms that there is a positive correlation between satisfaction level of relationships quality with supplier performance as an indicator of the effectiveness of key account management approach. The consistency of supplier firms and the key account manager on the relational behavior construct tend to increase satisfaction level of relationship quality and at the end increasing the supplier performance.Â Keywords: key account management, relationship marketing, relational behaviour, business to business marketing, poultry industry